2018
DOI: 10.1021/acsaem.7b00324
|View full text |Cite
|
Sign up to set email alerts
|

Anion De/Intercalation in Nickel Hydroxychloride Microspheres: A Mechanistic Study of Structural Impact on Energy Storage Performance of Multianion-Containing Layered Materials

Abstract: Electrochemical cation de/intercalation has long been investigated for energy-relevant applications, while anion de/intercalation is comparatively highly challenging, although promising for promoting the performance of materials. Herein, layered nickel hydroxychloride was selected as a model multianion-containing inorganic functional material to study. Hierarchical flower-like microspheres self-assembled from nanosheets were synthesized via a solvothermal method. The as-prepared nickel hydroxychloride was buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 61 publications
2
5
0
Order By: Relevance
“…Peaks a and b can be indexed to the Mn–O hybridization according to previous reports . CuMnO 2 obtained at 140 °C showed peak a at 528.6 eV, exhibiting an obvious shift toward higher energy at 529 eV when the crystal growth temperature exceeded 180 °C, which is originated from the rising valence state of Mn cations (Mn 2+ → Mn 3+ ), as reported previously. , On the basis of the crystal field theory, Mn 2+ has the electronic configuration of 3d 5 (t 2g 3 e g 2 ) and that of Mn 3+ is 3d 4 (t 2g 3 e g 1 ). So the electron will preferentially occupy the t 2g orbital of Mn 2+ with low energy (528.6 eV), while it will preferentially occupy the e g orbital of Mn 3+ with high energy (529 eV).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…Peaks a and b can be indexed to the Mn–O hybridization according to previous reports . CuMnO 2 obtained at 140 °C showed peak a at 528.6 eV, exhibiting an obvious shift toward higher energy at 529 eV when the crystal growth temperature exceeded 180 °C, which is originated from the rising valence state of Mn cations (Mn 2+ → Mn 3+ ), as reported previously. , On the basis of the crystal field theory, Mn 2+ has the electronic configuration of 3d 5 (t 2g 3 e g 2 ) and that of Mn 3+ is 3d 4 (t 2g 3 e g 1 ). So the electron will preferentially occupy the t 2g orbital of Mn 2+ with low energy (528.6 eV), while it will preferentially occupy the e g orbital of Mn 3+ with high energy (529 eV).…”
Section: Resultssupporting
confidence: 72%
“…A comparison of cyclic voltammetry (CV) curves (Figure a) of CuMnO 2 crystals was tested in a voltage range of 0–0.5 V at a scan rate of 50 mV/s. CV curves at different scan rates, i.e., 5, 10, 20, 50, and 100 mV/s of every electrode (Figure S3) showed typical redox peaks, implying ideal pseudocapacitive behaviors that involves reversible faradaic redox reactions of M-O/M-O–OH (M represents Cu and Mn) with the OH – ions in alkaline electrolyte. , Especially for the CuMnO 2 crystal obtained at 160 °C, the interval of redox peak positions significantly increased with the increasing scan rates, implying a dominant diffusion-controlled process during pseudocapacitive reaction, as reported elsewhere. , The diffusion-controlled process is only limited by the ion diffusion rate, so that controllable oriented growth of one-dimensional CuMnO 2 crystals can effectively liberate the surface limitation of the bulk material. A histogram (Figure b) that exhibited the graphing key indicators was given based on the comparative CV curves.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…24–26 It is found that anions can intercalate into the gallery of transition metal hydroxides to form intercalation compounds, increasing the interlayer spacing of products and affecting their electrochemical performance. 27–29 In particular, the intercalation compound (Ni(OH)–Cl) is found to enable it to further evolve into Ni(OH)Cl. 30 However, the effects of these anions on the microstructure, subsequent structural evolution, and structural characteristics of transition metal materials are still not clear.…”
Section: Introductionmentioning
confidence: 99%